Treatment of bacterial infections in obese adult patients: how to appropriately manage antimicrobial dosage. (October 2015) - Pai, Manjunath P
Highlights: A singular approach to antimicrobial dose selection in obese patients is not feasible. Total body weight based dosing risks over exposure and toxicity in obese patients. Alternate body size and kidney function based dosing serve as potential solutions. Abstract : Obese patients may require bigger initial antimicrobial doses but the optimal approach to maintenance dose selection is limited. Key pharmacokinetic system parameters are higher in obese patients but often not proportional to total body weight (TBW). Fixed-dose selection risks under exposure while TBW-based dosing risks over exposure in obese patients. Alternate body size descriptors limit overdosing in obesity that is vital for antimicrobials with a narrow therapeutic index. Maintenance dose calculation of antimicrobials in obese patients is challenging in the absence of therapeutic drug monitoring. Approaches to antimicrobial dose selection in obesity based on estimated kidney function serves as a lesser but clinically applicable alternative.